Can restoration of afforested peatland regulate pests and disease?. Issue 5 (7th August 2013) - Gilbert, Lucy
Summary: Government policies are driving landscape‐scale changes in land use to provide ecosystem services; but there may be unconsidered cascading effects. A major land use change targeted for regulating climate and biodiversity is peatland restoration. This will cause changes in vegetation and, potentially, keystone species such as large herbivores, which are the main hosts to Ixodes ricinus (L.) ticks, the most important vector of disease‐causing pathogens in Europe. This study tested the impact of restoring peatlands from conifer forestry on Ixodes ricinus abundance and explored the likely mechanisms. Large‐scale surveys of Ixodes ricinus, vertebrate herbivores and vegetation were conducted in adjacent areas of forest, bog and areas felled 5–13 years previously. Questing tick abundance was greatest in forest and almost absent from blanket bog, with intermediate numbers in felled areas, where ticks were more abundant in young than in old felled areas. The likely mechanisms for these variations in tick abundance were deer habitat preferences (bog was the least preferred habitat) and ground vegetation height or canopy cover, which are generally associated with alternative tick hosts and micro‐climates that aid tick questing and survival. Synthesis and applications . Felling conifer forest to restore peatlands could produce a dramatic decline in tick abundance throughout the restoration process, with implications for disease risk. Therefore, a further ecosystem service of peatlands in addition to climate, biodiversity and water regulation is regulating pests and disease. Deer management and procedures that speed up the restoration process are likely to enhance the effect during the intermediate stages. Abstract : Felling conifer forest to restore peatlands could produce a dramatic decline in tick abundance throughout the restoration process, with implications for disease risk. Therefore, a further ecosystem service of peatlands in addition to climate, biodiversity and water regulation is regulating pests and disease. Deer management and procedures that speed up the restoration process are likely to enhance the effect during the intermediate stages.